The Effect of Independent Commissioner, Dividend Policy, and Audit Quality on Firm Value: Empirical Evidence from the Basic Materials Sector in Indonesia (2020-2024) - Kristina Silalahi; Roy Budiharjo (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
The research empirically investigates the explanatory capacity of impact exerted by independent commissioner, dividend policy, and audit quality on firm value in basic materials firms, specifically focusing on business entities maintained as IDX-listed issuers during the 2020–2024 period. Utilizing a quantitative causal framework, a Random Effect Model was executed on 85 firm-year observations obtained from 17 purposively sampled corporations. To represent firm value, the analysis employs Tobin's Q. Meanwhile independent commissioner, dividend, and audit quality are operationalized via board proportions, dividend payout ratio, and a Big Four audit dummy, respectively. The empirical findings indicate that, partially, no statistically significant relationship was identified between independent commissioners and dividend policy. Conversely, a significant negative coefficient was identified for audit quality in explaining firm value. However, simultaneously, the joint interaction of all three variables significantly influences firm value. These outcomes imply that corporate governance and financial signals are interpreted contextually by investors in the basic materials sector, where broader industrial risks and operational dynamics often overshadow structural signals. Future studies are encouraged to incorporate broader financial indicators, such as profitability and leverage, to shed further light on the underlying mechanisms governing firm valuation in this sector.